ANALISIS HUBUNGAN ANTARA PENGETAHUAN, SIKAP, DAN PERILAKU KESEHATAN GIGI MULUT DENGAN ANGKA KARIES GIGI PADA MAHASISWA BARU FAKULTAS EKONOMI DAN BISNIS ISLAM UIN SUMATERA UTARA MEDAN - Hasibuan, Rahmayanti (Fakultas Kesehatan Masyarakat, Institut Kesehatan Deli Husada Deli Tua, 2024)
Dental caries is an oral health problem that is of global concern, where dental caries is a dental disease characterized by damage to the tooth surface and if left untreated, the infection extends to the pulp. The impact occurs changes in tooth structure, pain and infection and pulp death. There are 57 students out of 83 new undergraduate students in 2023 at the Faculty of Economics and Islamic Business experiencing dental caries, this case has always been a common dental problem, but must be reduced to a very low case. The purpose of the preparation of this study is to determine the relationship between knowledge, attitudes, and oral health behavior with dental caries rates in new students of the Faculty of Economics and Islamic Business UIN North Sumatra Medan. The method used in this study was observational analytic with a cross sectional approach, a sample of 287 respondents, data collection methods with observation and questionnaires. The results of this study show that there is a relationship between knowledge and dental caries rates (ρ = 0.000), there is a relationship between attitudes and dental caries rates (ρ = 0.000), and there is a relationship between behavior and dental caries rates (ρ = 0.000). The conclusion that behavior is the most dominant factor influencing the number of dental caries ρ = 0.002, OR value 26.903, and C.I 95% (3.250 - 222.684). It is recommended for the Faculty to make a policy with the university clinic in the form of an oral health program. Students are expected to know, be good, and apply oral health behavior.